Registration and Fusion of the Autofluorescent and Infrared Retinal Images - Radim Kolar; Libor Kubecka; Jiri Jan (International Journal of Biomedical Imaging)
This article deals with registration and fusion of multimodal opththalmologic images obtained by means of a laser scanning device (Heidelberg retina angiograph). The registration framework has been designed and tested for combination of autofluorescent and infrared images. This process is a necessary step for consecutive pixel level fusion and analysis utilizing information from both modalities. Two fusion methods are presented and compared.